Thyme travels: 15N isoscapes of Thymus vulgaris L. invasion in lightly grazed pastoral communities. (14th July 2015) - Nielsen, J. A.; Frew, R. D.; Whigham, P. A.; Callaway, R. M.; Dickinson, K. J. M.
Abstract: Alterations to ecosystem nitrogen (N) cycling by introduced plant species may increase the invasibility of habitat providing a positive feedback for the introduced species to become invasive. Spatial patterns of foliar and soil δ 15 N ratios reflect variation in rates and process of N‐cycling across invaded landscapes and provide insight into N‐source uptake and utilization strategies of invasive plant species. To evaluate invasion‐associated changes in soil and foliar δ 15 N at different scales: regional (among different sites), local (between north‐ and south‐facing aspect at the same site), and microsite (within populations in the same community), we measured foliar and soil δ 15 N, animal faeces cover (as a proxy for grazing intensity) and N2 ‐fixing species cover from inside to outside T hymus vulgaris L. (thyme)‐invaded lightly grazed pastoral communities in Central Otago, southern South Island, New Zealand. Mean thyme foliar δ 15 N were near‐zero across the invaded landscape, and did not change across the advancing edge of invasion or with aspect. There was no evidence that associations with N2 ‐fixing species provide a potential N source. Soil δ 15 N was lower inside of thyme compared to at the edge or outside of thyme and was varied between aspects at some sites. Animal faeces cover as a proxy for grazing intensity explained only 23% of this observed variation of soil δ 15 N. Thyme invasion may result in lowered soil δ 15 N reflecting alterations to N dynamics. Associated invasion‐related impacts of animal grazing may also impact soil δ 15 N. Further studies are required to distinguish the underlying mechanism responsible for the observed patterns of foliar and soil δ 15 N values across thyme‐invaded Central Otago landscapes.